1998
DOI: 10.1093/mutage/13.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic effect of crown ethers on heavy metal-induced sister chromatid exchanges

Abstract: Macrocyclic polyethers (crown ethers) are a family of compounds that possess the ability to complex with and transport metal ions across membranes. Because of their unique ionophoric characteristic, they have wide application in industry and research, chemistry and biology. In the current investigation the relationship between heavy metal mutagenesis and crown ether co-mutagenicity and/or antimutagenicity in mammalian cells has been examined using sister chromatid exchange (SCE) as the cytogenetic end point. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Because the studied structures possess neither a condensed aromatic moiety nor any positive charges, the absence of interaction with DNA is not surprising. These results are in accordance with Arenas et al showing that 18-crown-6 and 21-crown-7 and their dicyclohexyl derivatives are not genotoxic nor do they exhibit co-mutagenic properties …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Because the studied structures possess neither a condensed aromatic moiety nor any positive charges, the absence of interaction with DNA is not surprising. These results are in accordance with Arenas et al showing that 18-crown-6 and 21-crown-7 and their dicyclohexyl derivatives are not genotoxic nor do they exhibit co-mutagenic properties …”
Section: Resultssupporting
confidence: 93%
“…1 However, although some crown ether complexes with, for example, naphthoquinonethiol, 10 cisplatin derivatives, 11 or a bis-(propargilic) sulfone moiety, 12 showed good antitumor and/or antimicrobial activities, no systematic study has been performed on the potential antitumor ability of nonfunctionalized crown compounds. The fact that some crown ethers showed antiproliferative activity 13 and that some ionophores, such as valinomycin, an antibiotic with potassium-selective ionophoric activity, have been reported to display antitumor effects, together with the recent studies on the potential cytotoxicity caused by disrupted ion transport by Gokel group, 14,15 inspired us to check the possible antiproliferative/antitumor ability of crown ethers. We report the antiproliferative activity and structure-activity relationship of several conventional crown ethers and their derivatives in vitro and compare this activity to that of valinomycin.…”
Section: Introductionmentioning
confidence: 99%
“…This supported the concept that their toxicity is due to their interaction with membranes, and not with nucleic acids; they do not possess DNA‐damaging activity 68. 69 Moreover, it was shown that dicyclohexyl‐21‐crown‐7 has antimutagenic effects on heavy‐metal‐induced sister chromatid exchanges 70. More recently, Zasukhina et al.…”
Section: Biological Activity Of Crown Ethersmentioning
confidence: 72%
“…Interestingly, in all experiments described above, the crown ether moieties alone were not tested in parallel with the crown‐ether‐substituted derivatives in order to assess their independent activity. In general, there are limited reports on the antiproliferative activity of crown ethers in mammalian cells,70, 89 although it has been known for more than 20 years that ionophores such as valinomycin, an antibiotic with potassium‐selective ionophoric activity, have been reported to display strong antitumor effects 90. Its use has been limited by its extreme toxicity, yet it was shown that this toxicity could be decreased by incorporating valinomycin in liposomes, while maintaining or even enhancing its antitumor activity 91.…”
Section: Biological Activity Of Crown Ethersmentioning
confidence: 99%
“…MoA probably involves factors associated with DNA damage and repair, and with a membranotropic effect . Apoptotic pathways including preapoptotic genes are probably also involved …”
Section: Discussionmentioning
confidence: 99%